A history of American music education - Mark, Michael L.; Gary, Charles L.; MENC, the National Association for Music Education (U.S.) (Lanham, Md. : Rowman and Littlefield Education, 2007)
History of American Music Education covers the history of American music education, from its roots in Biblical times through recent historical events and trends. It describes the educational, philosophical, educational, and sociological aspects of the subject, always putting it in the context of the history of the United States. It offers the most complete information on professional organizations, materials, techniques, and personalities of any publication.
The ancient Jewish tradition -- The age of antiquity -- Music education from the early Christian era to the Reformation -- Early music education in the New World -- The New England roots of American music education -- Education for a new democracy -- The Pestalozzian education reform movement -- The beginnings of music in American schools -- Music education in an industrializing America -- The development of professional education organizations -- The beginning of the Music Educators National Conference -- The broadening music curriculum -- The Music Educators National Conference matures -- American education after 1950 -- Government, foundation, and not-for-profit support for arts education -- New foundations of music education -- New curricular foundations of music education -- The twenty-first century -- Reflections.
"Published in partnership with MENC, the National Association for Music Education."
Includes bibliographical references and index.
Keywords: Music -- Instruction and study -- United States